Analysis on Rational Choice of NW Anjani’s Community in Lombok Tengah Local Leader Election - Muh. Alwi Parhanudin (Politea : Jurnal Politik Islam, 2020)
Nahdlatul Wathan has three charitable enterprises (Amal Usaha) as its institutional central movement: education, social, and dakwah Islamiyah fields. Out of the three central movements, social field is interpreted most widely as the principle of justification for practical political development undertaken by Nahdlatul Wathan. Nahdlatul Wathan still develops its organizations consistently, including practical political domain until today. NW has encountered internal problem related to leadership dualism since 1998 until today: Anjani and Pancor versions. Dualism problem widens political dynamic of NW, particularly in NTB, with their own constructed direction and political development. This article discussed political dynamic of Anjani-version Nahdlatul Wathan in considering rational choice aspect of NTB community members. The dynamic was analyzed using rational choice theory as the primary theory, in addition to practical opportunity theory, framing process and resource mobilization as the reading instrument in analyzing the mechanism and procedure of succession taken by Nahdlatul Wathan. This study described that Nahdlatul Wathan Anjani has not maximized fully the political policy yet based on rational choice aspect of citizens, thereby affecting the objectivity of its political analysis in seeing opportunity structure, succession technique packaging, and political resource distribution.